145k views
4 votes
Please answer ASAP I will give you five stars

Please answer ASAP I will give you five stars-example-1
User Venimus
by
4.7k points

2 Answers

2 votes

Answer: (0, -1)

========================================================

Step-by-step explanation:

The notation
(x,y) \to (x-6, y-1) means that whatever the x coordinate is, we subtract 6 from it. At the same time, whatever the y coordinate is, we subtract 1 from it.

The point (x,y) = (6,0) means x = 6 and y = 0.

Therefore,


(x,y) \to (x-6, y-1)\\\\(6,0) \to (6-6, 0-1)\\\\(6,0) \to (0, -1)

Visually, the starting point (6,0) moves 6 units to the left and 1 unit down to arrive at (0,-1). See the diagram below.

Please answer ASAP I will give you five stars-example-1
User VeeDuvv
by
4.8k points
6 votes

Answer:

(0,-1)

Step-by-step explanation:

:)

User Polymath
by
5.0k points